2019
DOI: 10.1111/neup.12609
|View full text |Cite
|
Sign up to set email alerts
|

A case of diffuse midline glioma, H3 K27M mutant mimicking a hemispheric malignant glioma in an elderly patient

Abstract: Diffuse midline glioma, H3 K27M mutant arises from midline structures of the central nervous system and predominately affects pediatric patients. However, this disease entity was only recently established, and the clinical phenotypic spectrum remains largely unclear. We herein report a rare case of diffuse midline glioma, H3 K27M mutant with an unusual distribution in an elderly woman who presented with a diffuse glioma that invaded both sides of the thalami, and left hippocampus and frontoparietal lobes, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the frequency of elderly patients with DMG, H3 K27M-mut is notable [28,29]. We recently described an elderly patient with the DMG, H3 K27M-mut that mimicked a hemispheric malignant glioma [30]. Taken together, the H3 status of an adult hemispheric diffuse glioma affecting the midline should be confirmed even in elderly patients.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the frequency of elderly patients with DMG, H3 K27M-mut is notable [28,29]. We recently described an elderly patient with the DMG, H3 K27M-mut that mimicked a hemispheric malignant glioma [30]. Taken together, the H3 status of an adult hemispheric diffuse glioma affecting the midline should be confirmed even in elderly patients.…”
Section: Discussionmentioning
confidence: 89%
“…However, paediatric-type diffuse gliomas may also occur in adults, especially young adults. For example, many cases of “diffuse midline glioma, H3 K27-altered” have been reported in young adults ( 15 , 16 ), and cases have even been reported in patients over 60 years of age ( 17 , 18 ). Paediatric-type diffuse gliomas are IDH wt by definition ( 2 ), thus some of the entities are a consideration in adult patients with an IDH wt glioma, in particular H3 K27-altered and H3 G34-mutant gliomas (which demonstrate different changes in the H3 histone).…”
Section: Key Changes In the 2021 Who Classificationmentioning
confidence: 99%
“…Conversely, a glioma demonstrating H3 K27-alteration but no involvement of midline structures cannot be diagnosed as this entity ( 2 , 33 ). It is worthwhile noting that more disseminated tumours with a component of midline involvement may also harbour this molecular change ( 18 ), and such a pattern may not be apparent without close attention to the imaging. Beyond this, however, no features have yet been identified which can confidently suggest or exclude this genotype ( 16 ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…Nevertheless, these tumors can occasionally be larger. For example, out of 66 H3 K27Mmutant adult gliomas reported by Qiu et al, eight demonstrated cerebral hemispheric infiltration together with thalamic and/or brainstem involvement [22], and cases of extensive H3 K27M-mutant gliomas in older patients have been reported [33,36].…”
Section: Tumor Margins and Extentmentioning
confidence: 99%